Shift to private pension system: The case of Poland and Israel - Manor, Moshe; Ratajczak, Joanna (DEMO, 2020)
Following Chilean experiences as well as the World Bank suggestions post‑communistPoland and post-collectivist Israel—underwent deep reforms which ledto the privatization of old age security. The aim of the article is to compare the Polishand Israeli paths of pension privatization in the last thirty years. The main conclusionsare: (1) the economic, demographic and political environments at the momentof the design and implementation of the pension reform were quite similar in bothcountries; however (2) the scope and scale of the privatization was different: in Polandthere was only partial shift towards private pension system while in Israel full privatizationof the system was implemented; (3) the decisive factors were: the inertia of thealready existing pension systems and the power of foreign influencers; (4) the retreatfrom privatization in Poland and the increase in Israel took place due to the differentmix of disadvantages of the new pension arrangements, short-term political aims andinternational pressure.
Keywords: pension system; pension privatization; private pension system; Poland; Israel